Statistical and epidemiologic models in gastrointestinal cancers analysis - Pourhoseingholi, Mohamad Amin (Translational Gastrointestinal Cancer; Vol 3, No 4 (October 22, 2014): Translational Gastrointestinal Cancer (Biostatistics and Epidemiology Models in Gastrointestinal Cancers), 2014)
Cancer is known as one of the major causes leading to many disorders, death, and disabilities worldwide. Among all organ cancers, gastrointestinal (GI) cancers present an interesting pattern in distribution over the world. The epidemiology of cancer is the study of the factors affecting cancer, as a way to infer possible trends and causes. Statistical and epidemiological methods help us to find the cause of cancer and to identify and develop improved treatments. During the last two decades, epidemiology has undergone a rapid evolution toward collaborative research (1) and biostatistics is among the important scientific developments and growth in statistical methods for application to studies of medicine. Developments in likelihood methods for inference, epidemiologic statistics, clinical trials, survival analysis, and statistical genetics are beneficial for problems in public health, biomedical research and cancer studies.